The Effect of Financial Statement Quality on Investment Efficiency with Litigation Risk as a Moderating Variable - Febrianggi, Ayu; Razak, Linda Arisanty; Rayyani, Wa Ode (International Journal Labs, 2023)
This study aims to examine the effect of independent variables: the quality of financial statements (X) on investment efficiency (Y) with litigation risk as a moderating variable (Z) in manufacturing companies listed on the Indonesia Stock Exchange. The research method used is a quantitative method with an explanatory reseach approach. The population in this study is the financial report data of manufacturing companies listed on the IDX for 2018-2022 as many as 193 companies. The data collection technique in this study used purposive sampling techniques and produced sample samples of 39 manufacturing companies listed on the IDX for 5 years. Data analysis techniques that are processed using IBM SPSS Statistics. The results of this study show that the variable quality of financial statements is not negligible to investment efficiency. While the litigation risk variable is able to moderate the quality of financial statements on investment efficiency.